Heat but Not Cold Tolerance Is Phylogenetically Constrained in Greenlandic Terrestrial Arthropods Under Future Global Warming - Jonas Bruhn Wesseltoft; Nadieh de Jonge; Michael Møller Hansen; Toke Thomas Høye; Michael Ørsted; Torsten Nygaard Kristensen (Global Change Biology, 2026)
The Arctic is currently warming at up to four times the global average. Likewise, climate variability within and across seasons is predicted to markedly increase in the future. This may challenge organisms in these pristine environments, making it critically important to understand their thermal biology and evolutionary potential. For Arctic ectotherms in particular, thermal tolerance limits and responses to climate change are mostly unknown. Knowledge on this is urgently needed to enable prediction of climate change impacts on future distributions of biodiversity in these rapidly changing environments. Here, we provide data on upper and lower thermal limits of 93 Greenlandic species of insects, arachnids, and collembolans caught and tested in the field and identified using barcode sequencing. This represents ~8% of described terrestrial Greenlandic arthropod species. We found pronounced differences in heat and cold tolerance among species and a strong phylogenetic signal for both heat tolerance and thermal scope (difference between upper and lower thermal limits). We argue that this indicates a limited capacity for coping with increasing and more variable future temperatures through evolutionary adaptation. Further, we modelled future increases in microhabitat temperatures in our sampling area. We found that > 25% of the investigated species may periodically experience stressful high temperatures in the future. These results suggest that climate change will likely result in substantial changes in distributions and abundances of terrestrial arthropods in Southern Greenland.